Digital Twin Implementation of Autonomous Planning Arc Welding Robot System - Wang, Xuewu; Hua, Yi; Gao, Jin; Lin, Zongjie; Yu, Rui (Complex System Modeling and Simulation, 2023)
Industrial robots are currently applied for ship sub-assembly welding to replace welding workers because of the intelligent production and cost savings. In order to improve the efficiency of the robot system, a digital twin system of welding path planning for the arc welding robot in ship sub-assembly welding is proposed in this manuscript to achieve autonomous planning and generation of the welding path. First, a five-dimensional digital twin model of the dual arc welding robot system is constructed. Then, the system kinematics analysis and calibration are studied for communication realization between the virtual and the actual system. Besides, a topology consisting of three bounding volume hierarchies (BVH) trees is proposed to construct digital twin virtual entities in this system. Based on this topology, algorithms for welding seam extraction and collision detection are presented. Finally, the genetic algorithm and the RRT-Connect algorithm combined with region partitioning (RRT-Connect-RP) are applied for the welding sequence global planning and local jump path planning, respectively. The digital twin system and its path planning application are tested in the actual application scenario. The results show that the system can not only simulate the actual welding operation of the arc welding robot but also realize path planning and real-time control of the robot.